Analisis Potensi Investasi dan Strategi Promosi Peternakan Lampung - Prastya, Hendra (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study aims to analyze the investment potential of the livestock subsector in Lampung Province based on leading commodities, examine the gap between regional potential and actual investment realization, and formulate investment enhancement strategies using SWOT analysis and the Business Model Canvas (BMC) framework. Research Design and Methodology: The research employs a descriptive design with quantitative and qualitative approaches. Quantitative analysis includes assessing the contribution of the livestock subsector, investment efficiency using the ICOR, and identifying commodity potential through Location Quotient (LQ), livestock concentration (IKT), and carrying capacity (IDD). Qualitative analysis is performed through SWOT assessment and the development of a digital investment marketing model based on the Business Model Canvas. Data were sourced from BPS, BKPM, the Ministry of Agriculture, and regional policy documents. Findings and Discussion: The findings reveal that while the livestock subsector significantly contributes to Lampung’s regional economy, its investment realization remains low at around 0.24% of national investment in 2022. Beef cattle, goats, native chickens, and laying hens show strong comparative advantages and sizeable production gaps relative to projected consumption. Lampung possesses abundant feed resources, supported by a “Safe” Carrying Capacity Index.However, a high ICOR reflects inefficiencies in investment utilization. Key constraints include a limited local feed industry, insufficient digitalization of investment information, low competency in modern livestock management, and minimal digital or spatial-based investment promotion. The SWOT and BMC results highlight the need for a digital investment marketing platform, stronger partnerships, improved supporting infrastructure, and the development of a regional livestock investment brand such as “Lampung Livestock Safe-Haven.” Implications: The implication is that the most effective policy strategy for attracting quality and sustainable investment is to focus on strengthening digital marketing (through platforms like IPRO), establishing multi-stakeholder partnerships between investors and local farmers, and improving the investment information system. These crucial steps are necessary to transform the region's comparative advantage into a competitive advantage.